632 Diagnostic and prognostic performance of HFA-PEFF and H2FpEF scores in patients with cardiac amyloidosis. (8th December 2021) - Tomasoni, Daniela; Merlo, Marco; Aimo, Alberto; Porcari, Aldostefano; Angelis, Maria Grazia De; Longo, Francesca; Rossi, Maddalena; Nardi, Matilde; Vergaro, Giuseppe; Lombardi, Carlo Mario; Emdin, Michele; Sinagra, Gianfranco; et al.
Abstract: Aims: HFA-PEFF and H2 FPEF scores were developed to aid the diagnosis of heart failure with preserved ejection fraction (HFpEF) and have been associated with outcomes. We aimed to investigate the diagnostic and prognostic significance of these scores in patients with a specific phenotype of HFpEF, cardiac amyloidosis (CA). Methods and results: In a retrospective, double-centre, observational study we included 171 patients with either transthyretin (ATTR) ( n = 89, 52%) or light-chain (AL) ( n = 82, 48%) cardiac amyloidosis and preserved left ventricular ejection fraction (LVEF). Patients were divided into three groups according to HFA-PEFF score (low, 0–1; intermediate 2–4; high 5–6) and H2 FPEF score (low, 0–1; intermediate 2–5; high 6–9). None of the patients had a HFA-PEFF score of 0 or 1 ( n = 0, 0%); 57 (33.3%) patients had HFA-PEFF score 2–4 and the majority ( n = 114, 66.7%) had a high HFA-PEFF score. Twenty-eight (16.4%), 104 (60.8%), 39 (22.8%) patients had low, intermediate, and high H2 FPEF score, respectively. During a median follow-up of 14.5 (6.5–30.2) months after diagnosis, 61 (35.7%) patients died. Patients with a high HFA-PEFF score had higher mortality, compared to those with an intermediate score (47.4% vs. 12.3%, P < 0.001). After adjustment for several clinical variables, including age, sex, comorbidities, natriuretic peptides, troponin levels and echocardiographic parameters, a high HFA-PEFF score was independently associated with mortality (HR: 3.75; 95% CI: 1.61–8.70; P = 0.005). H2 FPEF score was not significantly associated with outcomes. Conclusions: Our results suggest that a low HFA-PEFF score successfully rules out CA diagnosis, whereas some CA patients present a low H2 FPEF score, potentially misleading the diagnosis. HFA-PEFF but not H2 FPEF score was associated with outcome in patients with CA.